P-032 Sperm parameters can predict the success of assisted reproductive technology. Single-center and retrospective analysis of assisted reproductive technology cycles from 1992 to 2020. (30th June 2022) - Melli, B; Morini, D; Spaggiari, G; Falbo, A.I; Lutzoni, R; Mezzadri, C; Di Girolamo, R.A.M; Daolio, J; La Sala, G.B; Romeo, M; Simoni, M; Aguzzoli, L; et al.
Abstract: Study question: Male parameters are largely underestimated in assisted reproductive technology (ART) success, so it was evaluated whether conventional semen parameters could predict assisted reproductive technology success Summary answer: Sperm motility plays a role in predicting in vitro fertilization (IVF) success, while sperm morphology is the relevant parameter in intracytoplasmic sperm injection (ICSI) cycles. What is known already: The detection of predictive markers would be very useful to choose the ART type and usually the male counterpart was relegated to a secondary role. Obviously, no convincing evidence that ART outcomes may be dependent on sperm parameters exists. The variation over the years of the reference values in semen analysis, together with the poor inter-laboratory standardization of sperm assessment, contributes to this very complex scenario. It remains undeniable that identifying thresholds of seminal parameters with prognostic significance in terms of pregnancy rate would have a considerable clinical impact in the assisted reproduction field. Study design, size, duration: A single-center, retrospective, observational study was carried out including couples attending the Santa Maria Nuova Hospital-IRCCS of Reggio Emilia for infertility between January 1992 and December 2020. Only fresh ART cycles performed in a single third-level fertility center were considered for this study with a total of 22, 013 cycles. Fertilization rate was the primary end-point, representing a parameter immediately dependent on male contribution. Pregnancy and live birth rates were considered in relation to semen variables. Participants/materials, setting, methods: Both partners were aged over 18 years and satisfied national criteria to access ART procedures. The studies considering common sperm parameters obtained by conventional semen analysis, that is, sperm number, motility, and morphology. Semen analyses were performed according to the World Health Organization (WHO) manual available at the time of the ART cycle. Ovarian stimulation was performed applying different hormone stimulating protocols and ART approach used are IVF or the ICSI. Main results and the role of chance: Considering the entire ART cohort, 5819 cycles were IVF (26.4%) and 16, 194 were ICSI (73.6%). Considering strong ART outcomes, the overall pregnancy rate was 20.4% (4, 368 cycles) for biochemical and 20.2% (4, 314 cycles) for clinical pregnancies, respectively. Among the latter, the overall live birth rate was 63.3%. Interestingly, both biochemical (20.8% vs. 19.1%, p < 0.001) and clinical (20.7% vs. 18.5%, p < 0.001) pregnancy rates were significantly higher in ICSI than IVF cycles. On the contrary, the live birth rate was not significantly different between ART methodologies (64.0% in ICSI vs. 60.9% in IVF, p = 0.074). Only 610 cycles (2.8%) were interrupted since no oocytes were retrieved after gonadotropins stimulation. Considering only cycles with oocytes retrieved, the fertilization rate was significantly higher in ICSI (42.4±39.7%) compared to IVF cycles (38.4±49.2%) (F = 27.343, p < 0.001). In IVF setting, both progressive motility (p = 0.012) and motility after capacitation (p = 0.002) significantly predicted the fertilization rate (statistical accuracy = 71.1%). Sperm motilities also predicted pregnancy (p < 0.001) and live birth (p = 0.001) rates. In ICSI, sperm morphology predicted fertilization rate (p = 0.001, statistical accuracy = 90.3%). Limitations, reasons for caution: These results, although statistically significant, show confidence intervals at the limits of significance. Therefore, this data must be carefully considered. From entering the ART path to its outcome, the variables encountered are numerous. The identification of a single parameter that influences, slightly, the final outcome, indicates a considerable clinical weight. Wider implications of the findings: Interestingly, sperm motility plays a role in predicting in vitro fertilization success, while sperm morphology is the relevant parameter in ICSI. These parameters may be considered reliable tools to measure the male role on ART outcomes, potentially impacting the clinical management of infertile couples. Trial registration number: not applicable